Long-term Respiratory Complication in Patients with Middle East Respiratory Syndrome: 1-year Follow-up After the 2015 Outbreak in South Korea. (4th October 2017) - Il Jun, Kang; Park, Wan Beom; Kim, Gayeon; Choi, Jae-Phil; Rhee, Ji-Young; Cheon, Shinhye; Park, Jun-Sun; Kim, Yeonjae; Joh, Joonsung; Chin, Bum Sik; Choe, Pyeong Gyun; Bang, Ji Whan; et al.
Abstract: Background: There are few data about long-term respiratory complications following Middle East Respiratory Syndrome coronavirus (MERS-CoV) infection. This study aimed to evaluate respiratory functions and radiologic sequelae according to the severity of infection one year after the patients experienced MERS-CoV infection. Methods: A total of 73 patients undergoing MERS-CoV infection during the 2015 MERS outbreak in South Korea were enrolled in this prospective multicenter study. Pulmonary function tests and 6-minute walking tests were performed 1 year after infection. Radiologic sequelae was defined as fibrosis or atelectasis on chest computer tomography and severe pneumonia was defined as that requiring oxygen therapy. Multivariate linear regression tests were used to evaluate the effect of infection severity on respiratory function. Results: At the time of MERS-CoV infection, 18 patients had no pneumonia, 35 experienced mild pneumonia, and 20 did severe pneumonia. The median age was not different between groups (P = 0.942). Forced vital capacity (FVC) was 102.6%, 94.9%, and 88.7% in the no, mild, and severe pneumonia group, respectively (P = 0.010) and forced expiratory volume in 1 second was 105.3%, 95.7%, and 91.7% (P = 0.057). Diffusing capacity (DLCO) was significantly lower in the severe pneumonia group than in the no or mild pneumonia group (78.3% vs. 89.4% or 88.6%, P = 0.035). In multivariate analyses, FVC and DLCO were significantly correlated with infection severity after adjustment with age, sex, underlying lung disease, and smoking. There was no difference in the walking distance of 6 minute tests between groups. Radiologic sequelae were shown in 18.8%, 65.6%, and 100% in the no, mild, and severe pneumonia group, respectively (P < 0.001). Conclusion: The patients with more severe pneumonia by MERS-CoV had more impaired respiratory function in one year follow-up, which was compatible with radiologic sequelae. Disclosures: All authors: No reported disclosures.